Selection of northern Yellowstone elk by gray wolves and hunters - Wright, Gregory J.; Peterson, Rolf O.; Smith, Douglas W.; Lemke, Thomas O. (Digital Commons @ Michigan Tech, 2006)
We compared selection of northern Yellowstone elk (Cervus elaphus) by hunters in the Gardiner Late Hunt and northern Yellowstone wolves (Canis lupus) with regard to sex, age, and impacts to recruitment. We compared harvest data from 1996-2001 with wolf-killed elk data from 1995-2001. We assessed the effects of hunting and wolf predation on reproductive female elk by constructing a life table and calculating reproductive values for females in the northern Yellowstone herd. We devised an index of total reproductive impact to measure impacts to calf production due to hunting and wolf predation. The age classes of female elk selected by wolves and hunters were significantly different. Hunters selected a large proportion of female elk with the greatest reproductive values, whereas wolves selected a large proportion of elk calves and older females with low reproductive values. The mean age of adult females killed by hunters throughout the study period was 6.5 years, whereas the mean age of adult females killed by wolves was 13.9 years. Hunting exerted a greater total reproductive impact on the herd than wolf predation. The combined effects of hunters killing prime-aged females (2-9 yr old), wolves killing calves, and predation by other predators has the potential to limit the elk population in the future. Yellowstone is unique in this regard because multiple predators that occur sympatrically, including hunters, wolves, grizzly bears (Ursus arctos), black bears (Ursus americanus), cougars (Felis concolor), and coyotes (Canis latrans), all prey on elk. Using an Adaptive Harvest Management process the known female elk harvest during the Gardiner Late Hunt has been reduced by 72% from 2,221 elk in 1997 to 620 elk in 2004. In the future, hunting harvest levels may be reduced further to partially offset elk losses to wolves, other predators, and environmental factors.